2018
DOI: 10.1186/s12870-018-1473-4
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a gene network in durum wheat roots exposed to cadmium

Abstract: BackgroundAmong cereals, durum wheat (Triticum turgidum L. subsp. durum) accumulates cadmium (Cd) at higher concentration if grown in Cd-polluted soils. Since cadmium accumulation is a risk for human health, the international trade organizations have limited the acceptable concentration of Cd in edible crops. Therefore, durum wheat cultivars accumulating low cadmium in grains should be preferred by farmers and consumers. To identify the response of durum wheat to the presence of Cd, the transcriptomes of roots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…S3) (61). Also, in durum wheat root (Triticum turgidum), cadmium treatment induced contigs having the highest similarity to Arabidopsis TAT1 and TAT2 by 20 -50 and 3 times, respectively (62). Notably, TAT2 expression is 40 times higher than TAT1 in WT under normal light conditions (Fig.…”
Section: In Vivo Functions and Localization Of Arabidopsis Tat1 And Tat2mentioning
confidence: 92%
“…S3) (61). Also, in durum wheat root (Triticum turgidum), cadmium treatment induced contigs having the highest similarity to Arabidopsis TAT1 and TAT2 by 20 -50 and 3 times, respectively (62). Notably, TAT2 expression is 40 times higher than TAT1 in WT under normal light conditions (Fig.…”
Section: In Vivo Functions and Localization Of Arabidopsis Tat1 And Tat2mentioning
confidence: 92%
“…Aprile et al [54] suggested that wheat with low Cd and Pb in leaves has a high expression of the gene YSL2 which has a possible regulatory role in Cd compartmentalization in roots. The YSL2 is localized to vacuole membranes and can transport metal-NA complexes [55]. In addition, DiDonato Jr. et al [56] stated that YSL2 is located in many cell types in the roots and shoots, suggesting that diverse cell types gain metals as metal-NA complexes.…”
Section: Phytotoxicity and Detoxification Mechanism In Wheatmentioning
confidence: 99%
“…The phylogeny of 136 WRKY proteins from the genus Glycyrrhiza displayed 22WRKYs (17GgWRKYs & 5GuWRKYs) belonging to group-I, 98 WRKYs (61 GgWRKYS & 37 GuWRKYs) clustering in group-II and 16 WRKY members comprising of group-III (4GgWRKYS & 12GuWRKYs). Group-II was further sub-divided into five sub-groups, IIa (11), IIb (17), IIc (16 + 8), IId (17), IIe (15) and an additional novel sub-group IIf (14) based on WRKY transcription factor rules adopted in Arabidopsis 9 . The present paper reports few exceptions observed in the WRKY members identified in the genus Glycyrrhiza.…”
Section: Phylogeny the Relatedness Among 136 Glycyrrhiza Wrky Proteimentioning
confidence: 99%